Pancasila As a Progressive Spirit of Character Development: Generation Z - Muhammad Irwawan Siswantoro; Danan Tricahyono (Pendekar: Jurnal Pendidikan Berkarakter, 2025)
Abstract: Generation Z faces the challenge posed by the diminishing significance of Pancasila values in defining the nation's identity. This article aims to examine the importance of Pancasila as a progressive spirit in shaping the character of the Indonesian nation based on Pancasila values. This study employs a qualitative methodology that focuses on literature review research. We collect data and information from articles, journals, and other primary and secondary data sources. The results of his research outline the values of each Pancasila precept and its relevance in the life of the nation and state, emphasizing the importance of respect for plurality, justice, unity, democracy, and social equality. Pancasila's progressive spirit plays a role in forming a tough, nationalist, and fair generation Z, with the aim of creating a national character based on Pancasila's values. This research has contributed to making Pancasila a value that lives in the joints of Generation Z's lives of Generation Z.Abstrak: Generazi Z menghadapi tantangan lunturnya nilai-nilai Pancasila sebagai kepribadian bangsa. Artikel ini memiliki tujuan mengkaji pentingnya Pancasila sebagai roh progresif dalam membentuk karakter bangsa Indonesia yang berdasarkan nilai-nilai Pancasila. Penelitian ini menggunakan metodologi kualitatif dengan jenis penelitian studi pustaka. Data dan informasi dikumpulkan dari artikel, jurnal, dan sumber data lainnya, baik primer maupun sekunder. Hasil penelitiannya menguraikan nilai-nilai setiap sila Pancasila dan relevansinya dalam kehidupan berbangsa dan bernegara, menekankan pentingnya penghormatan terhadap pluralitas, keadilan, persatuan, demokrasi, dan pemerataan sosial. Pancasila sebagai roh progresif berperan untuk membentuk generasi Z yang tangguh, nasionalis, dan berkeadilan, dengan tujuan menciptakan karakter bangsa yang berdasarkan nilai-nilai Pancasila. Penelitian ini memiliki kontribusi untuk menjadikan Pancasila sebagai nilai yang hidup dalam sendi-sendi kehidupan generazi Z.